Description of a new subspecies of Chonala laurae Bozano, 1999 from Southeastern China (Lepidoptera, Nymphalidae, Satyrinae) - Guo, Liang; Huang, Si-Yao; Wang, Min; Ma, Fang-Zhou (Zootaxa, 2023)
The satyrid species Chonala laurae Bozano, 1999, formerly only known from southern Shaanxi and western Hubei Provinces in the central part of China, is recorded from Mt. Wuyi, Fujian Province in southeastern China for the first time, and the population is described as a new subspecies herein: C. laurae wuyishana Huang, Guo & Wang, ssp. n. The new subspecies can be distinguished from the nominate one by the pattern at the costa and in space 2 on the forewing upperside in males and the ground color in females, and from the closely related C. houae by the coloration of the pattern on the forewing upperside and in space 2 on the forewing underside as well as the male genital character. A brief discussion on the relationship among C. laurae laurae, C. laurae wuyishana ssp. n., and C. houae is also presented. In addition, an updated key to species and subspecies of Chonala is provided.